PERDAGANGAN TERLARANG MENURUT ISLAM DALAM TINJAUAN MAQASHID AL-SYARI’AH - MS, Syaifullah (State Institute of Islamic Studies (IAIN) Palu, 2007)
Basically, in Islam, commerce is allowed unless there is a dalil (religious argument) that bans it. In Islamic perspective, commerce is one of central lives to achieve a piety. Therefore, in Islam, commerce is ethically regulated to avoid unfairness from those who involve in it. The purpose is that whoever involves in a commerce must be able to achieve a benefit from it. Even, Islam regulates not only the procedures of commerce transaction but also the objects of the commerce. This article deals with commerce banned in Islam based on maqashid al-syaria’h. Kata Kunci: Perdagangan, tadlis, spekulasi, maqashid al-syari’ah